Biomass environment functional material as well as preparation method and application thereof

By adding sulfurbausmium biochemical carbon to the pink of rice straw powder, and loading iron cobalt dual metals to form a composite catalyst, the problem of being easy to reunite with the CO-FE dual-metal catalysts, and realized the organic pollutants in the water body. Especially in the degradation rate of Cisciosa -star, it has performed well.

CN119346149APending Publication Date: 2025-01-24CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411445265.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art tends to cause catalyst agglomeration when using Co-Fe bimetallic catalysts, resulting in unsatisfactory catalytic efficiency and making it difficult to efficiently degrade organic pollutants in water bodies.

Method used

By mixing the rice straw powder with sulfur sulfur, the sulfur sulfur is prepared to modify the carbon, and the iron cobalt dual metal is loaded on its surface to form a composite catalyst, which overcomes the problem of catalyst reunion.

Benefits of technology

Improving the ability to degrade organic pollutants, especially in the application of actual water bodies, significantly improves the stability and efficiency of the catalyst, and the degradation rate of Cisciosa -Planceter reaches 87.5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346149A_ABST
    Figure CN119346149A_ABST
Patent Text Reader

Abstract

The invention discloses a biomass environment functional material as well as a preparation method and application thereof. The method comprises the following steps: preparing thiourea modified biochar by using rice straws as biomass, loading iron-cobalt bimetals on the basis of the thiourea modified biochar to prepare a composite environmental functional material, and degrading organic pollutants in wastewater by activating peroxymonosulfate (PMS). The method overcomes the agglomeration phenomenon of PMS catalyzed by Fe and Co bimetals, the environmental function material with good catalytic performance is prepared, and the degradation rate of ciprofloxacin reaches up to 87.5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental organic pollutant degradation, and specifically relates to a biomass environmental functional material and a preparation method and application thereof. Background Art

[0002] In recent years, with the development of quality of life and medical treatment, antibiotics are used more and more in medical and animal husbandry production. However, it is precisely because of the widespread use of antibiotics that some antibiotics that have not been digested and decomposed are discharged into natural water bodies, posing a serious threat to the human environment and life.

[0003] At present, there are many methods for treating water containing antibiotics, which can be divided into three categories: physical method, biological method and chemical method. Most methods for treating antibiotics are based on adsorption, but their adsorption capacity is limited and they are easily saturated during use. Therefore, advanced oxidation techniques (AOPs) have attracted more attention. AOPs have the characteristics of high oxidizing ability and fast reaction rate. Permonosulfate (PMS) is a strong oxidant that can produce a large number of active species during the reaction process: sulfate free radicals, hydroxyl free radicals and superoxide free radicals (SO4 -· .OH, O2 -· ) and play an important role in mineralizing pollutants into CO2 and H2O in a short time.

[0004] Considering the economic cost and environmental friendliness, a large number of researchers use transition metals as a catalytic method for PMS. Among them, iron (Fe) is a common transition metal, which has certain catalytic activity for PMS and is relatively environmentally friendly. Another transition metal, cobalt (Co), also has catalytic activity for PMS. Using single metal Co or Fe to activate PMS alone is not as effective as bimetallic (Co-Fe) activation. However, the use of Co-Fe bimetallic catalysts in a physical water environment can easily lead to catalyst agglomeration, resulting in the catalytic efficiency not reaching the ideal state (Analysis of electric field efficacy and remediation performance of triclosan contaminated soil by Co-Fe / al oxidation electrodes coupled with peroxymonosulfate (PMS) in an ECGO system with diversified electrode configurations, Chemosphere, 2022, 307: 135841).

[0005] In order to overcome this shortcoming, many carbon-based materials are used as catalyst carriers to evenly distribute metals on their surfaces and improve degradation efficiency and stability. Therefore, it is of great significance to study a new type of biomass environmental functional material. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a biomass environmental functional material and its preparation method and application in view of the deficiencies of the prior art. The present invention uses thiourea-modified biochar to load iron-cobalt bimetallic to prepare a biomass environmental functional material, which is used to activate persulfate to degrade organic pollutants in wastewater and improve the effluent water quality.

[0007] Technical solution: The purpose of the present invention is achieved through the following technical solution:

[0008] The present invention provides a method for preparing a biomass environmental functional material, comprising the following steps:

[0009] (1) uniformly mixing rice straw powder and thiourea, pyrolyzing, grinding, and sieving to obtain thiourea-modified biochar;

[0010] (2) washing and drying the thiourea-modified biochar obtained in step (1);

[0011] (3) The material obtained in step (2) is mixed with a cobalt-containing metal salt solution and an iron-containing metal salt solution, stirred, heated, washed, dried, and pyrolyzed to obtain the biomass environmental functional material.

[0012] The present invention uses rice straw, which is widely available and inexpensive, to prepare raw biochar. However, since the raw biochar has a small specific surface area and low porosity, thiourea is used to modify the raw biochar to increase the specific surface area and enrich the functional groups on the biochar, which is not only conducive to the distribution of Co-Fe bimetallic on the surface of the biochar, but also greatly improves the activation performance of PMS. Therefore, the iron-cobalt bimetallic is loaded on the thiourea-modified biochar, which overcomes the phenomenon of catalyst agglomeration in actual water bodies, improves the degradation ability of organic pollutants, and has important practical significance for the actual treatment of organic pollutants in wastewater.

[0013] Preferably, in step (1), the rice straw powder is washed with water and dried before use to obtain rice straw powder with impurities removed, i.e., raw biochar.

[0014] More preferably, the drying temperature is 85-120°C, for example, it can be 85°C, 87°C, 90°C, 94°C, 98°C, 100°C, 105°C, 110°C, 115°C or 120°C.

[0015] The drying time is 12 to 20 hours, for example, 12 hours, 13 hours, 15 hours, 18 hours or 20 hours.

[0016] Preferably, in step (1), the mass ratio of the rice straw powder to thiourea is 1-2:2-1.

[0017] Preferably, in step (1), the pyrolysis is carried out in the presence of an inert gas, the pyrolysis temperature is 500 to 800° C., and the pyrolysis time is 1 to 5 hours.

[0018] In the present invention, during the pyrolysis process in the presence of an inert gas, thiourea and rice straw powder undergo a chemical reaction, and the N and S elements in the thiourea are fixed in the biochar, so that the surface functional groups in the biochar increase, resulting in an increase in the specific surface area, which is beneficial to the subsequent loading of the iron-cobalt bimetallic. The environmental functional material prepared in this way has a good catalytic effect.

[0019] Further preferably, the inert gas is nitrogen, and the flow rate of the nitrogen is controlled at 60-80 mL / min.

[0020] More preferably, the heating rate of the pyrolysis is 5-10°C / min.

[0021] In the present invention, by controlling the pyrolysis temperature and the flow rate of nitrogen, the N and S content in the thiourea, the amount of biochar doped, the amount of functional groups and the morphological and structural characteristics are regulated to achieve better catalytic performance. If the pyrolysis temperature and the flow rate of nitrogen are inappropriate, the prepared environmental functional material cannot reach the ideal state, which is not conducive to the loading of the iron-cobalt bimetallic, so that its catalytic performance is poor, which will cause a waste of raw materials.

[0022] Preferably, in step (1), the size of the sieve used for sieving is 100 to 300 meshes.

[0023] Preferably, in step (2), the washing solvent is anhydrous ethanol and water; the drying temperature is 85 to 120° C.; and the drying time is 12 to 20 hours.

[0024] Preferably, in step (3), the cobalt-containing metal salt is cobalt nitrate hexahydrate, and the iron-containing metal salt is ferric nitrate nonahydrate; the molar ratio of the cobalt nitrate hexahydrate to the ferric nitrate nonahydrate is 1-2:2-1; and the mass ratio of the material obtained in step (2) to the cobalt nitrate hexahydrate is 1:2.

[0025] Preferably, in step (3), the heating temperature is 70-80°C, and the heating time is 1-2 hours; the pyrolysis temperature is 500-800°C, and the pyrolysis time is 1-5 hours.

[0026] In the present invention, thiourea-modified biochar is obtained by uniformly mixing rice straw powder with thiourea, and the modified biochar is mixed with cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and ferric nitrate nonahydrate (Fe(NO3)3·9H2O) and stirred, and then heated in a water bath, followed by suction filtration and washing, and the solid powder is placed in a tubular furnace for pyrolysis to prepare the biomass environmental functional material. The preparation method is simple and easy, and the prepared environmental functional material can be used as a catalyst.

[0027] Preferably, in step (3), the washing is performed 3 to 5 times; the drying temperature is 85 to 120° C.; and the drying time is 12 to 20 hours.

[0028] It is particularly important to note that drying is required after each washing.

[0029] Preferably, in step (3), the stirring time is 0.5 to 1 h; the stirring speed is 100 to 400 rpm.

[0030] A specific preferred embodiment of the present invention is that the method for preparing the biomass environmental functional material comprises the following steps:

[0031] (1) washing the rice straw powder with water, and drying it at 85 to 120° C. for 12 to 20 hours to obtain the rice straw powder from which impurities are removed;

[0032] (2) uniformly mixing the rice straw powder obtained in step (1) with thiourea, pyrolyzing the mixture under an inert nitrogen atmosphere at a flow rate of 60 to 80 mL / min and a heating rate of 5 to 10° C. / min, the pyrolysis temperature being 500 to 800° C. and the pyrolysis time being 1 to 5 h, and then grinding the mixture and sieving the mixture using a sieve with a size of 100 to 300 meshes to obtain thiourea-modified biochar;

[0033] (3) washing the thiourea-modified biochar obtained in step (2) with anhydrous ethanol and water alternately, filtering, and drying at 85 to 120° C. for 12 to 20 hours;

[0034] (4) adding the material obtained in step (3) with cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and ferric nitrate nonahydrate (Fe(NO3)3·9H2O) into water and mixing and stirring for 0.5 to 1 h, and then placing in a water bath at 70 to 80°C for 1 to 2 h;

[0035] (5) repeatedly washing the material obtained in step (4) with water and drying at 85 to 120° C. for 12 to 20 h;

[0036] (6) Pyrolyzing the material obtained in step (5) at 500-800° C. for 1-5 hours to obtain the biomass environmental functional material.

[0037] The present invention also provides a biomass environmental functional material prepared by the above preparation method. The biomass environmental functional material is a thiourea-modified biochar loaded with an iron-cobalt bimetallic catalyst, and iron-cobalt, as a metal catalyst, has a greater catalytic ability for PMS.

[0038] The present invention also provides the use of the above biomass environmental functional material as a catalyst in activating persulfate to degrade organic pollutants. The biomass environmental functional material of the present invention can be used for catalytic degradation of organic pollutants in wastewater.

[0039] Preferably, the added amount of the biomass environmental functional material is 0.05-1 g / L; the concentration of the organic pollutants is 20-160 mg / L; and the concentration of the persulfate is 0-6 mM.

[0040] Specifically, the biomass environmental functional material of the present invention is used as a catalyst to catalyze the degradation of organic pollutants in wastewater, such as ciprofloxacin, with a ciprofloxacin concentration of 20 to 160 mg / L, for example, 20 mg / L, 30 mg / L, 50 mg / L, 70 mg / L, 100 mg / L, 120 mg / L, 150 mg / L or 160 mg / L.

[0041] Beneficial effects:

[0042] The present invention uses rice straw as biomass to prepare thiourea modified biochar (NS-800), and loads iron and cobalt bimetallics on the modified biochar to prepare a composite environmental functional material (CoFe@NS-800), and degrades organic pollutants in wastewater by activating peroxymonosulfate (PMS). In the present invention, thiourea and rice straw powder are co-heat-treated, and N and S elements in thiourea can be doped into biochar to complete the exogenous doping of biochar materials; and the loading of Fe and Co bimetallics is completed by cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and iron nitrate nonahydrate (Fe(NO3)3·9H2O), thereby overcoming the phenomenon of agglomeration of Fe and Co bimetallic catalyzed PMS, thereby preparing an environmental functional material with good catalytic performance, and the degradation rate of ciprofloxacin is as high as 87.5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a scanning electron microscope image of the thiourea-modified biochar NS-800 prepared in Example 1 of the present invention;

[0044] Figure 2 This is a scanning electron microscope image of the biomass environmental functional material CoFe@NS-800 prepared in Example 1 of the present invention;

[0045] Figure 3TEM scanning image of the biomass environmental functional material CoFe@NS-800 prepared in Example 1 of the present invention;

[0046] Figure 4 X-ray diffraction spectra of thiourea-modified biochar NS-800 and biomass environmental functional material CoFe@NS-800 prepared in Example 1 of the present invention;

[0047] Figure 5 N2 adsorption-desorption isotherm curve and pore size distribution diagram of the biomass environmental functional material CoFe@NS-800 prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0048] The technical solution of the present invention is described in detail below through specific embodiments, but the protection scope of the present invention is not limited to the embodiments.

[0049] Example 1 Preparation of biomass environmental functional materials

[0050] (1) The rice straw powder was washed with ultrapure water and dried at 85° C. for 12 h to obtain the rice straw powder from which impurities were removed.

[0051] (2) The powder obtained in step (1) was uniformly mixed with thiourea in a mass ratio of 2:1, and pyrolyzed at a flow rate of 70 mL / min and a heating rate of 10°C / min under an inert gas nitrogen atmosphere. The pyrolysis temperature was 800°C and the pyrolysis was performed for 2 h. The mixture was then ground and sieved using a 100-mesh sieve to obtain thiourea-modified biochar, which was recorded as NS-800.

[0052] (3) The material obtained in step (2) was washed alternately with anhydrous ethanol and ultrapure water, filtered, and dried at 85° C. for 12 h.

[0053] (4) Add 0.3 g of the material obtained in step (3) and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) in a mass ratio of 1:2, and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and ferric nitrate nonahydrate (Fe(NO3)3·9H2O) in a molar ratio of 1:2 into 50 mL of water, mix and stir for 0.5 h, and place in a 70°C water bath for 1 h.

[0054] (5) The material obtained in step (4) was repeatedly washed with ultrapure water for 3 times and dried at 85°C for 12 h.

[0055] (6) The material obtained in step (5) is pyrolyzed at 500° C. for 1 h to obtain the biomass environmental functional material, which is denoted as CoFe@NS-800.

[0056] The microscopic surface morphology of the thiourea modified biochar (NS-800) and the biomass environmental functional material (CoFe@NS-800) provided in this embodiment was tested using a scanning electron microscope, and the biomass environmental functional material was characterized using a transmission scanning electron microscope. The test structures are as follows: Figure 1-3 shown.

[0057] Depend on Figure 1 It can be seen that the surface of thiourea-modified biochar has an irregular and uneven pore structure. Figure 2 It can be seen that the surface of biochar is covered with many tiny metal particles with uneven distribution in the pores, showing obvious pore structure and fragmentation characteristics. Figure 3 It can be seen that the metal particles are irregularly distributed in the pore structure, which further proves that the composite material loaded with iron-cobalt bimetallic materials based on this biochar is successfully loaded.

[0058] The thiourea modified biochar (NS-800) and biomass environmental functional material (CoFe@NS-800) provided in this embodiment were characterized by an X-ray diffraction spectrometer, and the X-ray diffraction spectra thereof are as follows: Figure 4 shown.

[0059] Depend on Figure 4 It can be seen that in addition to the characteristic diffraction peak of the graphite (002) plane at 2θ=20-30°, the biomass environmental functional material provided in this embodiment also shows a strong peak at 2θ=44.6°, indicating that the modified biochar has good crystallinity and is rich in a large number of N and S functional groups, thereby expanding the specific surface area and making it easier for metals to be loaded on the catalyst. Six diffraction peaks appear at 2θ values ​​of 30.2°, 35.4°, 43.3°, 53.6°, 57.1°, and 62.8°. They correspond to (220), (311), (400), (422), (511), and (440) of CoFe2O4, respectively. The XRD spectrum results show that Co and Fe are successfully loaded on thiourea-modified biochar.

[0060] Micromeritics ASAP2460 was used to test the pore size distribution of the thiourea modified biochar (NS-800) and the biomass environmental functional material (CoFe@NS-800) provided in this embodiment. The test results are as follows: Figure 5 shown.

[0061] Depend on Figure 5 It can be seen that the pore size of the biomass environmental functional material provided in this embodiment is mainly concentrated at about 5 nm, which is a mesoporous material. The specific surface area of ​​the material is greatly improved, providing favorable conditions for degrading organic pollutants.

[0062] Application Example 1

[0063] The biomass environmental functional material CoFe@NS-800 prepared in Example 1 was applied to actual aquaculture wastewater (taken from Hualiang Poultry and Animal Husbandry Base in Menghe, Changzhou) and medical wastewater (taken from Yourui Pharmaceutical Technology Co., Ltd., Changzhou). In actual application, the dosage of environmental functional material was 0.4 g / L, the concentration of peroxymonosulfate (PMS) was 2 mM, and 40 mL of actual wastewater was taken.

[0064] The total TOC content in aquaculture wastewater is 71.5 mg / L. After 60 minutes of reaction, the TOC content is 25.2 mg / L. The mineralization rate of organic pollutants in aquaculture wastewater by CoFe@NS-800 / PMS reaches 65%, and the degradation rate of the antibiotic ciprofloxacin in the wastewater is 90.7%.

[0065] For medical wastewater with a total TOC content of 15.9 mg / L, after activation by CoFe@NS-800 for 60 minutes, the total TOC content was 6.42 mg / L, the mineralization rate reached 59.6%, and the degradation rate of ciprofloxacin reached 87.6%, proving that this functional material is of great significance for removing organic pollutants in actual wastewater.

[0066] Application Example 2

[0067] The biomass environmental functional material CoFe@NS-800 prepared in Example 1 was added at a dosage of 0.2 g / L, the concentration of permonosulfate (PMS) was increased from 0 mM to 6 mM, and the concentration of ciprofloxacin was 50 mg / L. Interval sampling was performed within 60 min (5, 10, 15, 20, 30, 40, 60 min), and the concentration of ciprofloxacin was determined by liquid chromatography (HPLC).

[0068] Detection conditions: Polaris C18-A-Agilent liquid chromatography column was used, set at a wavelength of 275 nm, a column temperature of 30°C, mobile phase A was 0.3% formic acid solution, mobile phase B was acetonitrile, the flow rate was 1 mL / min, and the injection volume was 10 μL.

[0069] After 60 minutes of reaction, the degradation rate of ciprofloxacin increased from 58.2% to 87.5% without adding persulfate.

[0070] Example 2 Preparation of biomass environmental functional materials

[0071] Referring to the preparation method of Example 1, the only difference from Example 1 is that in step (2), the nitrogen flow rate is 65 mL / min and the heating rate is 6° C. / min; other conditions are the same as in Example 1, and the biomass environmental functional material is prepared.

[0072] According to the functional material dosage of 0.2g / L, the persulfate concentration of 2mM, the interval sampling (5, 10, 15, 20, 30, 40, 60min) was carried out within 60min, and the concentration of ciprofloxacin was measured by liquid phase (HPLC), and the detection conditions were: using Polaris C18-A-Agilent liquid chromatography column, set at a wavelength of 275nm, a column temperature of 30°C, a mobile phase A of 0.3% formic acid solution, a mobile phase B of acetonitrile, a flow rate of 1mL / min, and an injection volume of 10μL. The final degradation rate of ciprofloxacin was 78.2%.

[0073] Example 3 Preparation of biomass environmental functional materials

[0074] Referring to the preparation method of Example 1, the only difference from Example 1 is that in step (2), the nitrogen flow rate is 75 mL / min and the heating rate is 8° C. / min; other conditions are the same as in Example 1, and the biomass environmental functional material is prepared.

[0075] The application implementation method is consistent with Example 2, and the degradation rate of ciprofloxacin is 81.6%.

[0076] Example 4 Preparation of biomass environmental functional materials

[0077] Referring to the preparation method of Example 1, the only difference from Example 1 is that in step (2), the nitrogen flow rate is 60 mL / min and the heating rate is 5° C. / min; other conditions are the same as in Example 1, and the biomass environmental functional material is prepared.

[0078] The application implementation method is consistent with Example 2, and the degradation rate of ciprofloxacin is 77.4%.

[0079] Example 5 Preparation of biomass environmental functional materials

[0080] Referring to the preparation method of Example 1, the only difference from Example 1 is that the pyrolysis temperature in step (2) is set to 600° C. and the pyrolysis time is 2 h; other conditions are the same as those in Example 1, and the biomass environmental functional material is prepared.

[0081] The application implementation method is consistent with Example 2, and the degradation rate of ciprofloxacin is 69.8%.

[0082] Example 6 Preparation of biomass environmental functional materials

[0083] (1) The rice straw powder was washed with ultrapure water and dried at 85° C. for 12 h to obtain the rice straw powder from which impurities were removed.

[0084] (2) The powder obtained in step (1) was uniformly mixed with thiourea in a mass ratio of 1:1, and pyrolyzed at a flow rate of 70 mL / min and a heating rate of 10°C / min under an inert gas nitrogen atmosphere. The pyrolysis temperature was 800°C and the pyrolysis was performed for 2 h. The mixture was then ground and sieved using a 100-mesh sieve to obtain thiourea-modified biochar.

[0085] (3) The material obtained in step (2) was washed alternately with anhydrous ethanol and ultrapure water, filtered, and dried at 85° C. for 12 h.

[0086] (4) Add 0.3 g of the material obtained in step (3) and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) in a mass ratio of 1:2, and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and ferric nitrate nonahydrate (Fe(NO3)3·9H2O) in a molar ratio of 2:1 into 50 mL of water, mix and stir for 0.5 h, and place in a 70°C water bath for 1 h.

[0087] (5) The material obtained in step (4) was repeatedly washed with ultrapure water and dried at 85°C for 12 h.

[0088] (6) The material obtained in step (5) is pyrolyzed at 600° C. under nitrogen protection for 1 h to obtain the environmental functional material.

[0089] The application implementation method is consistent with that of Example 2. After testing, the environmental functional material prepared in this example is finally pyrolyzed at 600°C for 1h in step (6). The degradation rate of ciprofloxacin by the finally obtained CoFe@NS-800 activated PMS is 72.3%.

[0090] Example 7 Preparation of biomass environmental functional materials

[0091] (1) The rice straw powder was washed with ultrapure water and dried at 85° C. for 12 h to obtain the rice straw powder from which impurities were removed.

[0092] (2) The powder obtained in step (1) was uniformly mixed with thiourea in a mass ratio of 1:2, and pyrolyzed at a flow rate of 70 mL / min and a heating rate of 10°C / min under an inert gas nitrogen atmosphere. The pyrolysis temperature was 800°C and the pyrolysis was performed for 2 h. The mixture was then ground and sieved using a 100-mesh sieve to obtain thiourea-modified biochar.

[0093] (3) The material obtained in step (2) was washed alternately with anhydrous ethanol and ultrapure water, filtered, and dried at 85° C. for 12 h.

[0094] (4) Add 0.3 g of the material obtained in step (3) and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) in a mass ratio of 1:2, and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and ferric nitrate nonahydrate (Fe(NO3)3·9H2O) in a molar ratio of 1:1 into 50 mL of water, mix and stir for 0.5 h, and place in a 70°C water bath for 1 h.

[0095] (5) The material obtained in step (4) was repeatedly washed with ultrapure water and dried at 85°C for 12 h.

[0096] (6) Pyrolyzing the material obtained in step (5) at 500° C. under nitrogen protection for 1 h to obtain the environmental functional material.

[0097] The application implementation method is consistent with that of Example 2. After testing, the environmental functional material prepared in this example, the degradation rate of CoFe@NS-800 activated PMS for ciprofloxacin is 70.4%.

[0098] Comparative Example 1

[0099] This comparative example provides an environmental functional material and a preparation method, which is different from Example 1 in that, in this comparative example, thiourea modification is not used, and the original biochar is used to load the iron-cobalt bimetallic, and other conditions are the same as those in Example 1. The experiment shows that the degradation rate of ciprofloxacin is 52.6%.

[0100] Comparative Example 2

[0101] Referring to the preparation method of Example 1, the difference from Example 1 is that the thiourea-modified biochar prepared in step (2) is directly used to activate PMS to degrade ciprofloxacin, and the other conditions are the same as those in Example 1.

[0102] (1) The rice straw powder was washed with ultrapure water and dried at 85° C. for 12 h to obtain the rice straw powder from which impurities were removed.

[0103] (2) The powder obtained in step (1) was uniformly mixed with thiourea in a mass ratio of 2:1, and pyrolyzed at a flow rate of 70 mL / min and a heating rate of 10°C / min under an inert gas nitrogen atmosphere. The pyrolysis temperature was 800°C and the pyrolysis was performed for 2 h. The mixture was then ground and sieved using a 100-mesh sieve to obtain thiourea-modified biochar.

[0104] The experiment showed that the degradation rate of ciprofloxacin was 47.3%.

[0105] Comparative Example 3

[0106] Referring to the preparation method of Example 1, the difference from Example 1 is that the pyrolysis temperature of the biochar in step (2) is set to 450°C, the pyrolysis time is 2 hours, the pyrolysis temperature in step (6) is the same as that in Example 1, and the other conditions are the same as those in Example 1, and the biomass environmental functional material is prepared.

[0107] The experimental comparison shows that the degradation rate of ciprofloxacin at this temperature is 62.7%. Compared with Example 1, if the pyrolysis temperature of the prepared environmental functional material is too low, the catalytic performance of the prepared environmental functional material is poor.

[0108] Comparative Example 4

[0109] Referring to the preparation method of Example 1, the difference from Example 1 is that the pyrolysis is not directly carried out under the action of nitrogen. It is observed that many white particles appear on the surface of the pyrolyzed biochar, which may be white crystalline particles left by the reaction of thiourea with air during the pyrolysis process. The degradation rate of ciprofloxacin by the biochar obtained by this method is 63.4%.

[0110] As described above, although the present invention has been shown and described with reference to specific preferred embodiments, it should not be construed as limiting the present invention itself. Various changes in form and details may be made without departing from the spirit and scope of the present invention as defined in the appended claims.

Claims

1. A method for preparing a biomass environmental functional material, characterized in that: The steps include: (1) uniformly mixing rice straw powder and thiourea, pyrolyzing, grinding, and sieving to obtain thiourea-modified biochar; (2) washing and drying the thiourea-modified biochar obtained in step (1); (3) The material obtained in step (2) is mixed with a cobalt-containing metal salt solution and an iron-containing metal salt solution, stirred, heated, washed, dried, and pyrolyzed to obtain the biomass environmental functional material.

2. The preparation method according to claim 1, characterized in that: In step (1), the mass ratio of the rice straw powder to thiourea is 1-2:2-1.

3. The preparation method according to claim 1, characterized in that: In step (1), the pyrolysis is carried out in the presence of an inert gas, the pyrolysis temperature is 500 to 800° C., and the pyrolysis time is 1 to 5 hours.

4. The preparation method according to claim 3, characterized in that: The inert gas is nitrogen, and the flow rate of the nitrogen is controlled at 60-80 mL / min.

5. The preparation method according to claim 1, characterized in that: In step (2), the washing solvent is anhydrous ethanol and water; the drying temperature is 85 to 120° C.; and the drying time is 12 to 20 hours.

6. The preparation method according to claim 1, characterized in that: In step (3), the cobalt-containing metal salt is cobalt nitrate hexahydrate, and the iron-containing metal salt is ferric nitrate nonahydrate; the molar ratio of the cobalt nitrate hexahydrate to the ferric nitrate nonahydrate is 1-2:2-1; and the mass ratio of the material obtained in step (2) to the cobalt nitrate hexahydrate is 1:

2.

7. The preparation method according to claim 1, characterized in that: In step (3), the heating temperature is 70-80°C, and the heating time is 1-2 hours; the pyrolysis temperature is 500-800°C, and the pyrolysis time is 1-5 hours.

8. The biomass environmental functional material prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the biomass environmental functional material according to claim 8 as a catalyst in activating persulfate to degrade organic pollutants.

10. The use according to claim 9, characterized in that: The added amount of the biomass environmental functional material is 0.05-1 g / L; the concentration of the organic pollutants is 20-160 mg / L; and the concentration of the persulfate is 0-6 mM.